2005
DOI: 10.1007/s00440-005-0461-4
|View full text |Cite
|
Sign up to set email alerts
|

On the recurrence of edge-reinforced random walk on ℤ×G

Abstract: Let G be a finite tree. It is shown that edge-reinforced random walk on Z × G with large initial weights is recurrent. This includes recurrence on multi-level ladders of arbitrary width. For edge-reinforced random walk on {0, 1, . . . , n} × G, it is proved that asymptotically, with high probability, the normalized edge local times decay exponentially in the distance from the starting level. The estimates are uniform in n. They are used in the recurrence proof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…This simplifies considerably the present proof compared to the previous papers [5,7,11]. In those papers, the estimates for the contributions from the spanning trees were quite involved.…”
Section: Deforming the Random Environmentmentioning
confidence: 87%
See 3 more Smart Citations
“…This simplifies considerably the present proof compared to the previous papers [5,7,11]. In those papers, the estimates for the contributions from the spanning trees were quite involved.…”
Section: Deforming the Random Environmentmentioning
confidence: 87%
“…The later development indeed followed this idea: In [5], it was shown that the edge-reinforced random walk on the ladder Z × {1, 2} with all initial weights equal to the same constant b > 3/4 is recurrent. For the edge-reinforced random walk on Z×T with a finite tree T and constant large initial weights, recurrence was shown in [11]. In [7], a more detailed analysis of the edge-reinforced random walk with large constant initial weights on N 0 × {1, 2} and on N 0 × T with a finite tree T was given.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The following result was proved in [22]. The result was extended in [29], under the assumption the initial weight a is large: Theorem 7.2. Let G be a finite tree.…”
Section: Reinforced Random Walk On Laddersmentioning
confidence: 97%